2019
DOI: 10.1186/s13568-019-0767-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular authentication and differentiation of Dendrobium species by rDNA ITS region sequence analysis

Abstract: Owing to their significant medicinal and edible values, the natural Dendrobium species have underdone over-collection and habitat destruction, and cultivated species emerged for candidates. However, these Dendrobium plants are similar in shape to be easily confused, leading to extreme difficulties for identification based on their morphological and chemical features. In this study, the rDNA ITS region sequence analysis was developed for rapid and accurate identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
2
11
0
2
Order By: Relevance
“…Among those barcoding regions, ITS was the most commonly used. [2,8,9,14,15,25,[36][37][38][39]. Our results again confirmed the effect of ITS in the evaluation of genetic diversity and the identification of Dendrobium species not only in Southern Vietnam but also in other habitats.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Among those barcoding regions, ITS was the most commonly used. [2,8,9,14,15,25,[36][37][38][39]. Our results again confirmed the effect of ITS in the evaluation of genetic diversity and the identification of Dendrobium species not only in Southern Vietnam but also in other habitats.…”
Section: Discussionsupporting
confidence: 82%
“…ITS was also used in previous studies on identification of Dendrobium species, among which some studies focused on medicinal species for distinguishing herbals and their adulterants [13,14]. In a previous study of Tran et al (2018) [15], 19 out of 23 Vietnamese Dendrobium species (82.61%) were identified using the ITS marker (Appendix E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the previous methods have many disadvantages to test the expression of the DNA methylation markers due to the complicated process, high cost, inaccurate results and so on. According to the previous researches, we concluded that ARMS-PCR technique is a classical and well-developed method to genotype SNPs [4]. The principle of this technique to detect DNA methylation is to design two forward allele-specific primers that can target methylation status and unmethylation status, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is still little information on pollination of the Dendrobium species. Many species of Dendrobium are morphologically very similar to each other, however, some species have overlapping morphological differences that may result in misidentifications [ 6 , 7 ]. In this case, the classical methods of identification that rely on distinguishing characteristic features visible to the naked eye are not sufficient.…”
Section: Introductionmentioning
confidence: 99%